The Effect of Gayatri Mantra Meditation on Blood Pressure Reduction in Elderly Individuals with Hypertension in Pemecutan Kelod Village, Denpasar, Indonesia - Dewi, Ni Putu Diah Trisna; Sudiantara, Ketut; Mustika, I Wayan; Ngurah, I Gusti Ketut Gede; Suardana, I Wayan; Lestari, Agus Sri (Knowledge Dynamics, 2025)
Background: Hypertension is one of the most common cardiovascular diseases experienced by many elderly people. This study intends to assess the impact of Gayatri Mantra meditation on lowering blood pressure in elderly hypertension in Banjar Abiantimbul, Pemecutan Kelod Village, Denpasar, Indonesia. Methods: This study used a pretest and posttest research design. The samples consisted of 20 participants in the intervention group and 20 in the control group. The meditation intervention was carried out for 3 weeks, with a frequency of two sessions a week, each lasting 15 minutes. Results: Before the intervention, 55% of participants in the intervention group had Stage 2 hypertension, while 60% in the control group had Stage 1 hypertension. After the intervention, 70% of the intervention group experienced a reduction in blood pressure to Stage 1, whereas the control group exhibited no significant change. A paired sample t test showed a p-value of 0.000 (<0.05), indicating a statistically significant effect. Conclusions: The study concludes that Gayatri Mantra meditation significantly reduces blood pressure in elderly individuals with hypertension in Banjar Abiantimbul, Pemecutan Kelod Village, Denpasar, Indonesia. These results suggest that meditation-based interventions could be integrated into hypertension management programs for elderly populations.